Reading Sign as a Response to an Architectural Work (Case study: Wisma Garuda) - Imam Faisal Pane; Hilma T Fachrudin; Hesti Fibriasari; Aurora S Lubis (Britain International for Academic Research (BIAR) Publisher, 2020)
Between objects and observers in the world of architecture have a close relationship. In assessing and appreciating an architectural work it is necessary to synchronize architectural objects as a sign. The sign in question means an architectural work that functions as a sentence that can be read and has a meaning or meaning. The position of an architectural work depends on the observer in appreciating it. In general, this paper explains that an architectural object has an understanding that can be understood by the observer in accordance with the appreciation reached to the observer. The object under study was Wisma Garuda, a budget hotel. Where the hotel applies the concept of experience in architecture, but it reads as Buddhist philosophy by the curator of the Indonesian Pavilion 2018. Even though the architect of the building does not use Buddhist philosophy, based on an analysis of the interconnectedness of Husserl's and Buddha's philosophy it proves that the meaning received by the curator is something natural.